Harold Wilson, 'Selsdon Man', and the defence of social democracy in 1970s Britain. (1st October 2021) - Sloman, Peter
Abstract: Harold Wilson's attack on 'Selsdon Man' in the run-up to the 1970 general election has generally been seen as a flawed rhetorical gambit, which inadvertently gave coherence to Edward Heath's policies. The subsequent invocation of 'Selsdon' by critics of Heath's 'u-turns' has meant that the episode has mainly attracted scrutiny from historians of the Conservative Party. Yet the debate over Selsdon can also be seen as a landmark in Wilson's transition from the 'modernizing' politics of the 1960s to a more defensive posture, in which he presented Labour as a bulwark against regressive market-liberal policies. This article explores Wilson's critique of the 'new Conservatism' and argues that the themes which he established in 1970 played an important role in framing Labour's opposition to the Heath government during the subsequent Parliament. In particular, his focus on the distributional effects of Tory policies dovetailed with an emerging body of social science research on income and wealth and so contributed to a 'rediscovery of inequality'. In the turbulent economic climate of the mid-1970s, however, Labour's efforts to protect working-class households from the effects of market pricing proved difficult to sustain in office. The rise and fall of this politics of 'decommodification' has important implications for our understanding of the changing fortunes of British social democracy.